Macrophage recruitment and epithelial repair following hair cell injury in the mouse utricle - Kaur, Tejbeer; Hirose, Keiko; Rubel, Edwin W.; Warchol, Mark E. (Frontiers in Cellular Neuroscience, 2015)
The sensory organs of the inner ear possess resident populations of macrophages, but the function of those cells is poorly understood. In many tissues, macrophages participate in the removal of cellular debris after injury and can also promote tissue repair. The present study examined injury-evoked macrophage activity in the mouse utricle. Experiments used transgenic mice in which the gene for the human diphtheria toxin receptor (huDTR) was inserted under regulation of the Pou4f3 promoter. Hair cells in such mice can be selectively lesioned by systemic treatment with diphtheria toxin (DT). In order to visualize macrophages, Pou4f3-huDTR mice were crossed with a second transgenic line, in which one or both copies of the gene for the fractalkine receptor CX3CR1 were replaced with a gene for GFP. Such mice expressed GFP in all macrophages, and mice that were CX3CR1GFP/GFP lacked the necessary receptor for fractalkine signaling. Treatment with DT resulted in the death of ~70% of utricular hair cells within seven days, which was accompanied by increased numbers of macrophages within the utricular sensory epithelium. Many of these macrophages appeared to be actively engulfing hair cell debris, indicating that macrophages participate in the process of ‘corpse removal’ in the mammalian vestibular organs. However, we observed no apparent differences in injury-evoked macrophage numbers in the utricles of CX3CR1+/GFP mice vs. CX3CR1GFP/GFP mice, suggesting that fractalkine signaling is not necessary for macrophage recruitment in these sensory organs. Finally, we found that repair of sensory epithelia at short times after DT-induced hair cell lesions was mediated by relatively thin cables of F-actin. After 56 days recovery, however, all cell-cell junctions were characterized by very thick actin cables.